Rancang Bangun Sistem Sandar Otomatis Menggunakan Arduino - Sony Gunawan; Diana Alia; Jaka Septian Kustanto (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
This applied scientific work is entitled "Design of Automatic Smart Berthing System Based on Arduino". Ships are a comfortable alternative transportation. Currently, ship development is needed so that they can operate properly. During the docking process, ship accidents often occur in ports both nationally and internationally. Therefore, a better development or safety is needed that can be given to ships during the docking process. This tool uses the Arduino Nano microcontroller as the main control and an ultrasonic sensor as a distance counter to prevent accidents. This applied scientific work aims to realize and facilitate work on the ship by abandoning manual methods. Berthing is the location of the ship's mooring or security, the area around the ship where the anchor is thrown, the ship's residence, employing the ship's crew and positioning the ship in the desired place. This scientific paper uses experimental research as its research method. The use of experimental research methods in educational research will be faced with problems concerning research subjects. Experimental research is also research that is carried out intentionally by researchers by providing certain treatments to research subjects in order to create a tool or design that is expected by the researcher.